Urban Microclimates in a Warming World: Land Surface Temperature (LST) Trends Across Ten Major Cities on Seven Continents - Yiğitalp Kara; Veli Yavuz (Urban Science)
Understanding microclimatic changes driven by urbanization is critical in the context of global warming and climate change. This study investigates the land surface temperature (LST), the normalized difference vegetation index (NDVI), and changes in land use types for 10 major cities across seven continents between 2001 and 2021. Utilizing MODIS satellite data processed on the Google Earth Engine (GEE) platform, the analysis focused on yearly median values to examine variations in LST during the day and night, as well as temperature dynamics across different land types, including vegetation and bare land. The global mean LST trend from 2001 to 2021, derived from Terra MODIS MOD11A2 data, was found to be 0.025 °C/year. The analysis of daytime and nighttime (nocturnal) land surface temperature (LST) trends across the ten cities examined in this study reveals notable variations, with most cities exhibiting an increasing trend in LST within urban mosaics. Airports exhibited a mean daytime land surface temperature (LST) that was 2.5 °C higher than surrounding areas, while industrial zones demonstrated an even greater temperature disparity, with an average increase of 2.81 °C. In contrast, cold spots characterized by dense vegetation showed a notable cooling effect, with LST differences reaching −3.7 °C. Similarly, proximity to water bodies contributed to temperature mitigation, as areas near significant water sources recorded lower daytime LST differences, averaging −4.09 °C. A strong negative correlation was found between NDVI and LST, underscoring the cooling effect of vegetation through evapotranspiration and shading. This study provides a comprehensive global perspective on the commonalities of urban temperature dynamics in cities across diverse geographical regions and climates, contributing to a deeper understanding of how urbanization and land use changes influence surface temperatures and climate change.